Antimicrobial susceptibility profile and detection of extended spectrum β-lactamase resistance genes in pseudomonas aeruginosa isolated from post-operative wounds - Ja’afaru, M I; Bashir, M; Tizhe, F F; Kachalla, N A (Journal of Diseases, 2023)
The spread of Pseudomonas aeruginosa is difficult to control with disinfectants and antibiotics due to the resistance found in P. aeruginosa isolates. The study investigated the susceptibility profile and detect extended spectrum β-lactamase (ESBL) resistance genes in the Pseudomonas aeruginosa isolated from post-operative wound infection. Wound swabs were cultured on MacConkey and sub-cultured on Cetrimide agar. The isolates were identified base on their macroscopic and microscopic characteristics as well as 16SrRNA. Disc diffusion technique was used to check the susceptibility profile of the isolates and the extended spectrum beta-lactam (ESBL) producers were determined by growing the isolates on Mueller Hinton agar plate in the presence of amoxyclav. 40 positive isolates were recovered in the study with 21 isolates been multi-drug resistance (MDR). Before plasmid curing, Streptomycin, ceftazidime, Augmentin, and Gentamicin has the highest resistance rate of 80% (n=32), 60% (n=24), 60% (n=24) and 60% (n=24) respectively. However, after plasmid curing, the result showed reduction in resistance rates. Streptomycin and ceftazidime showed high reduction in resistance from 80% to 25% and from 60 to 12.7% respectively indicating that resistance was plasmid-mediated. Pseudomonas aeruginosa F23 and Pseudomonas aeruginosa S15 isolates shown to possess both the plcH and bla PER genes with bands amplicons size of 307bp and 520bp respectively. Antibiotic susceptibility pattern after plasmid curing showed that 45% of the isolates produces beta-lactamase enzymes i.e., 18 out of 40 isolates were inactive to all beta-lactam group of antibiotics.